A review of the issues and challenges involved in using participant‐produced photographs in nursing research. (10th February 2015) - Balmer, Claire; Griffiths, Frances; Dunn, Janet
Abstract Aims To discuss the issues and challenges that may occur when using participant‐produced photographs in nursing research. Background The place of visual representation in society is increasingly being recognized and there is a growing discussion on the advantages of implementing visual methods, such as photography, in health and illness research. Integrating photographs has much potential for both nurse researchers and participants but it remains a novel method of gathering qualitative data and many aspects have had little consideration in the nursing and medical literature. This paper presents a discussion of some of the issues that may arise when using photographs as data. It draws on examples of the insights and experiences we had when we asked study participants to produce photographs to complement their interviews designed to explore their experience of living after cancer. Design Discussion paper Data sources This paper is based on our own experiences and supported by literature and theory. Implications for nursing Disseminating this research has prompted much interest from nurses and clinical staff. This paper should highlight some of the factors that may need to be addressed before employing such a novel method, thus ensuring the research process is positive and the outcome relevant for all parties. Conclusion Examples are used here to illustrate practical, ethical and philosophical issues around the research plan, creating and interpreting photographic data, confidentiality and copyright and analysing and disseminating photographs produced for research.